YURAK-QON TOMIR TIZIMI KASALLIKLARIDA HAMSHIRALIK PARVARISHI. - Sherg’oziyeva Hilola Kamolxon qizi; Narimonova Muhayyo Hikmatjon qizi; Ergashev Otabek Murotjon o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Cardiovascular diseases are diseases of the heart, arteries, and veins. They are numerous and diverse. Some of these diseases (rheumatism, myocarditis, etc.) affect the heart, some affect the arteries (atherosclerosis) or veins (for example, thrombophlebitis), and others affect the entire cardiovascular system (hypertension). Cardiovascular surgical care plays a critical role in the management of patients with surgical conditions affecting the heart and blood vessels. Due to the complex nature of these conditions, a range of techniques and interventions must be utilized to ensure optimal patient outcomes. This article discusses the importance of cardiovascular surgical care.